2010
DOI: 10.1124/dmd.110.035121
|View full text |Cite
|
Sign up to set email alerts
|

Human CYP2S1 Metabolizes Cyclooxygenase- and Lipoxygenase-Derived Eicosanoids

Abstract: ABSTRACT:CYP2S1 is a recently described dioxin-inducible cytochrome P450. We previously demonstrated that human CYP2S1 oxidizes a number of carcinogens but only via the peroxide shunt. In this article, we investigated whether human CYP2S1 can metabolize cyclooxygenase-and lipoxygenase-derived lipid peroxides in a NADPHindependent fashion. Human CYP2S1 metabolizes prostaglandin ), respectively. Other cytochromes P450 such as CYP1A1, 1A2, 1B1, and 3A4 underwent similar conversions but at slower rates. The fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 44 publications
3
63
0
4
Order By: Relevance
“…The endogenous function and contribution of CYP2S1 to xenobiotic metabolism has not yet been fully described, although recent studies have suggested a role in lipid peroxidation (Bui et al, 2011). Original dot blot analysis revealed high CYP2S1 expression in the lung, trachea, small intestine, spleen, and gut (Rylander et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endogenous function and contribution of CYP2S1 to xenobiotic metabolism has not yet been fully described, although recent studies have suggested a role in lipid peroxidation (Bui et al, 2011). Original dot blot analysis revealed high CYP2S1 expression in the lung, trachea, small intestine, spleen, and gut (Rylander et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although CYP2S1 shares molecular characteristics with both CYP1 and CYP2 family enzymes, lack of detailed knowledge of substrate specificity had classified CYP2S1 as an "orphan" cytochrome P450 (P450), along with CYP2W1 and other recently discovered P450s . However, recent data suggest a role for CYP2S1 in the metabolism of cyclooxygenase-and lipoxygenase-derived eicosanoids (Bui et al, 2011) and in activation of the anticancer drug AQ4N (Nishida et al, 2010), although these studies present opposing views on the ability of CYP2S1 to interact with the key electron donor NADPH P450 reductase (CPR).…”
Section: Introductionmentioning
confidence: 98%
“…Our results are important, because this is the fi rst report to quantitatively show TxAS-independent 12-HHT production using TxAS-defi cient mice. Recently, Bui et al reported that cytochrome P450 protein CYP2S1 is able to metabolize PGG 2 and PGH 2 to 12-HHT ( 31 ). Further study is required to identify the other 12-HHT-producing enzymes.…”
Section: Involvement Of Cox-1 and Txasmentioning
confidence: 99%
“…The activity of recombinant human CYP2S1 has been studied in several laboratories (e.g., Smith et al, 2003;Karlgren et al, 2005;Wang et al, 2005;Wu et al, 2006). Although the results from these studies were sometimes conflicting, CYP2S1 appears to have limited ability in vitro to catalyze NADPH-dependent oxidative metabolism (e.g., Wu et al, 2006); however, it is effective in catalyzing NADPH-independent, hydroperoxide or lipid peroxidesupported oxidation of many xenobiotic and endogenous compounds (Bui et al, 2009(Bui et al, , 2011. Furthermore, CYP2S1 could be reduced by P450 reductase and is efficient in metabolizing certain drugs in an NADPH-dependent fashion under hypoxic conditions (Nishida et al, 2010;Xiao et al, 2011).…”
Section: Mousementioning
confidence: 99%